Thermal cycling failure of the multilayer thermal barrier coatings based on LaMgAl11O19/YSZ. Issue 4 (April 2020) - Chen, Xiaolong; Sun, Yiwei; Hu, Jinkang; Li, Jie; Deng, Chunming; Wu, Duoli; Zeng, Dahai; Li, Wei; Liu, Ying; Zou, Binglin; Cao, Xueqiang
Abstract: Thermal cycling failure of three multilayer TBCs based on LaMgAl11 O19 (LaMA)/YSZ was comparatively investigated by using the burner-rig testing method in this work. Results indicate that through optimizing the weight ratio and thickness of the intermediate LaMA/YSZ composite layers, a five-layer TBC with much improved thermal cycling life of 11, 749 cycles at 1372 °C surface and 1042 °C bond coat testing temperature has been realized. While, thermal cycling lifetimes of the tri- and six-layer TBCs were 7439 and 7804 cycles at surface/bond coat testing temperatures of 1378 °C/1065 °C and 1367 °C/1056 °C, respectively. Factors related to the 60 wt.% LaMA + 40 wt.% YSZ (60LaMA + 40YSZ) intermediate composite layer with the highest thermal expansion coefficient than other composite layers generating higher internal stress level to the tri- and six-layer TBCs, different bond coat temperature and TGO growth, as well as long-term stability of the LaMA coating during thermal cycling tests, were characterized and compared to understand the different thermal cycling lifetime and failure modes among such three multilayer TBCs.